Rebuilding war-torn states the challenge of post-conflict economic reconstruction - Castillo, Graciana del. (Oxford : Oxford University Press, 2008)
With public attention increasingly focused on efforts to reconstruct war torn countries like Iraq and Afghanistan, this text looks at the unique set of challenges faced by such countries in the transition to peace.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Postwar reconstruction; Postwar reconstruction -- Economic aspects